Effects of nonspecific resistance in barley genotypes obtained by cell selection - O. N. Shupletsova; S. Yu. Ogorodnikova; Ya. I. Nazarova (Труды по прикладной ботанике, генетике и селекции)
An effective way to increase the genetic diversity of plants and create sources of resistance to edaphic stressors is the selection of cells under selective in vitro conditions based on somaclonal variation. The use of somaclones (regenerant forms) of barley with resistance to increased acidity, ionic toxicity of aluminum, heavy metals and drought is promising in the northeast of the Non-Black-Soil Zone of Russia. Development of regenerants with integrated resistance to soil stressors due to specific and nonspecific mechanisms is a relevant trend.The target research material was a hybrid combination of spring barley (Luly × Conrad) × 2867-80 and its regenerant forms obtained as a result of cell selection with stressors of various nature. Plants were grown under ordinary soil conditions and on provocative backgrounds with aluminum and cadmium. The productive traits of plants, the symptoms of oxidative stress, and the environment-forming activity of the root system were evaluated.In regenerated plants obtained in callus culture on selective in vitro media with aluminum or water deficiency, an increased ability of the root system to alkalize the medium in the rhizosphere zone (by 0.2–0.5 pH units) when grown on alumina soil was revealed. Against stressful soil backgrounds, regenerative lines induced on in vitro media with cadmium or aluminum were observed to have a low manifestation of oxidative stress symptoms, tested by the intensity of lipid peroxidation and the content of photosynthetic pigments in the leaves, which provided these genotypes with higher seed productivity (1.5–3.6 times in the number of grains, and 1.5– 3.0 times in the grain weight per plant) and adaptive advantages compared to the original genotype and regenerants induced on an in vitro medium with water deficiency. It is concluded that complex resistance to soil aluminum and cadmium toxicity is formed in barley regenerants obtained in the process of cell selection on in vitro media with any of these metals.